Still Minding the Gap-Inflation Dynamics during Episodes of Persistent Large Output Gaps - Meier, Andre (IMF Working Papers; Working Paper ;, 2010)
This paper studies inflation dynamics during 25 historical episodes in advanced economies where output remained well below potential for an extended period. We find that such episodes generally brought about significant disinflation, underpinned by weak labor markets, slowing wage growth, and, in many cases, falling oil prices. Indeed, inflation declined by about the same fraction of the initial inflation rate across episodes. That said, disinflation has tended to taper off at very low positive inflation rates, arguably reflecting downward nominal rigidities and well-anchored inflation expectations. Temporary inflation increases during episodes were, in turn, systematically related to currency depreciation or higher oil prices. Overall, the historical patterns suggest little upside inflation risk in advanced economies facing the prospect of persistent large output gaps.